Practical training report (ADS666): Asajaya District Office (Pejabat Daerah Asajaya) / Azrena Syarezan Ryaduan - Ryaduan, Azrena Syarezan (University Technology MARA Sarawak, 2015)
Asajaya is a small town located in Sarawak Samarahan Division. Most of the population is made up of Malays, Chinese and Iban and an area of lowlands consisting of mangrove forests. This area has four secondary schools namely SMK Asajaya, SMK Semera, SMK Pansantren Abdul Taib Mahmud and SMK Asajaya 2. Agriculture is the main economic sector and an important population activities in Asajaya. This area is also known as Permanent Food Production Park. Therefore, this sector contributes as a supplier of raw materials to the daily needs, market and downstream economic activities whether for local or overseas market. With the Drainage and Irrigation project in Asajaya, it was beneficial to all farmers, coconut, cocoa and citrus. The area is among the most fertile areas in Sarawak and was developed intensively.